2020
DOI: 10.1108/jefas-03-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Identifying fiscal inflation in India: some recent evidence from an asymmetric approach

Abstract: Purpose Among the many factors fueling the inflationary tendencies in an economy such as monetary shocks, structural shocks, demand shocks, external shocks and demographic changes, the issue of inflation (INF) has also been found to be related to fiscal policy decisions of the government. The purpose of this study is to investigate the inflationary tendencies in India particularly from the fiscal point of view. The study also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Using the mean group and pooled mean group estimators within the panel Autoregressive Distributed Lag (ARDL) framework, results showed that budget deficits are significant drivers of inflation among high-inflation and developing country groups, but not among low-inflation advanced economies. These results are consistent with a wide range of literature that shows the positive dynamic relationship between budget deficits and inflation (Bhat and Sharma, 2020; Nguyen, 2015; Lin and Chu, 2013).…”
Section: Literature Reviewsupporting
confidence: 92%
“…Using the mean group and pooled mean group estimators within the panel Autoregressive Distributed Lag (ARDL) framework, results showed that budget deficits are significant drivers of inflation among high-inflation and developing country groups, but not among low-inflation advanced economies. These results are consistent with a wide range of literature that shows the positive dynamic relationship between budget deficits and inflation (Bhat and Sharma, 2020; Nguyen, 2015; Lin and Chu, 2013).…”
Section: Literature Reviewsupporting
confidence: 92%
“…Granato et al (2007) and Abbaspour et al (2011). It is contradicted by Romer's hypothesis that inflation would decrease with openness (Alfaro, 2005;Gruben and McLeod, 2004); Bhat and Sharma, 2020;Lin et al, 2017 andAfzal et al, 2013). The positive relationship indicates that the Sudan economy depends on imports, especially luxury goods.…”
Section: Estimation Of Asymmetric Nardl Resultsmentioning
confidence: 93%
“…Additionally, positive effects were found on inflation and exchange rates, money supply and the consumer price index. Bhat and Sharma (2020) employed the nonlinear autoregressive distributed lag (NARDL) technique for the period from 1970 to 2015. They found that the positive coefficient of economic openness on inflation in the longterm was insignificant, and these results refuted those found by (Romer, 1993), while the negative coefficient of economic openness on inflation in the long-term was statistically significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study holds that the role of output gap via demand pressures in explaining price level is more significant than the money supply, interest rate and exchange rate. Bhat and Sharma (2020) in an asymmetric procedure shows that output growth and interest rate has inflation dampening effect which fiscal deficit and openness has inflationary impact in the Indian context over the period 1970-2016. Romer (1993 argues that economies that are more open tends to have low rate of inflation.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%